PERAN AMBIGUITAS DALAM MEMODERASI PENGARUH PENGALAMAN, KECERDASAN EMOSIONAL DAN ETIKA PROFESI TERHADAP KUALITAS AUDIT PADA AUDITOR INTERNAL BPR DI PROVINSI JAWA TENGAH - Grace Rusitha; Astohar Astohar (UNIVERSITAS DHARMAWANGSA, 2026)
This research investigates the effects of auditor experience, emotional intelligence, and professional ethics on audit quality, while also testing ambiguity as a moderating factor among internal auditors of BPR institutions in Central Java Province. A quantitative design was employed using a simple random sampling technique. Primary data were gathered from 94 BPR internal auditors through structured questionnaires. The analysis was conducted using multiple linear regression together with moderation regression testing. The findings demonstrate that experience, emotional intelligence, and professional ethics each have a positive and statistically significant impact on audit quality. Furthermore, ambiguity plays a moderating role in the relationships between those three variables and audit quality. The results highlight that individual auditor attributes are critical drivers of audit quality, whereas unclear role conditions do not eliminate their influence within the internal audit setting of BPR’s. This study adds to the audit literature in the microfinance sector and offers practical insights for BPR management and regulators in designing policies to strengthen audit quality